Does Objective Structured Clinical Examinations Score Reflect the Clinical Reasoning Ability of Medical Students?. (July 2015) - Park, Wan Beom; Kang, Seok Hoon; Lee, Yoon-Seong; Myung, Sun Jung
Abstract: Background: Clinical reasoning ability is an important factor in a physician's competence and thus should be taught and tested in medical schools. Medical schools generally use objective structured clinical examinations (OSCE) to measure the clinical competency of medical students. However, it is unknown whether OSCE can also evaluate clinical reasoning ability. In this study, the authors investigated whether OSCE scores reflected students' clinical reasoning abilities. Methods: Sixty-five fourth-year medical students participated in this study. Medical students completed the OSCE with 4 cases using standardized patients. For assessment of clinical reasoning, students were asked to list differential diagnoses and the findings that were compatible or not compatible with each diagnosis. The OSCE score (score of patient encounter), diagnostic accuracy score, clinical reasoning score, clinical knowledge score and grade point average (GPA) were obtained for each student, and correlation analysis was performed. Results: Clinical reasoning score was significantly correlated with diagnostic accuracy and GPA (correlation coefficient = 0.258 and 0.380; P = 0.038 and 0.002, respectively) but not with OSCE score or clinical knowledge score (correlation coefficient = 0.137 and 0.242; P = 0.276 and 0.052, respectively). Total OSCE score was not significantly correlated with clinical knowledge test score, clinical reasoning score, diagnostic accuracy score or GPA. Conclusions: OSCE score from patient encounters did not reflect the clinical reasoning abilities of the medical students in this study. The evaluation of medical students' clinical reasoning abilities through OSCE should be strengthened.